The Implementation of Merdeka Belajar Curriculum At English Department of Indonesian Universities - Sri Wahyuni; Ima Fitriyah; Imroatul Hasanah (JEELS (Journal of English Education and Linguistics Studies), 2023)
This article aims at investigating the implementation of Merdeka Belajar curriculum at some English Language Education of Indonesian universities. The stake holders of English Language Education Study Programs of a State University in Malang and a State Islamic Institute in Kediri are purposely selected as the subject of the study. In addition, semi structured interview and documentation are used to collect the data. The data collected in this study are analyzed based on Miles and Huberman’s interactive model of data analysis. The finding shows that both institutions have different terms in the implementation. English Language Education Study Program of a State University in Malang uses terms adaptive curriculum with MBKM (Merdeka Belajar Kampus Merdeka) programs without changing the existing curriculum used. Differently, English Language Education Study Program of a State Islamic Institute in Kediri develops a new curriculum which is compatible with MBKM policy. The new curriculum is developed from the existing curriculum, KKNI, and inserting the MBKM programs in the new curriculum structure